2021
DOI: 10.1002/csr.2171
|View full text |Cite
|
Sign up to set email alerts
|

Green ambidexterity and environmental performance: The role of green human resources

Abstract: Recent literature in the domain of environmental management suggests that employees' behavior is vital to enhance environmental performance. Despite this, little effort has been made to study how human resource management is linked with the environmental performance. Even less attention has been given to a joint consideration of green innovation and green human resources management and their

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0
8

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 116 publications
4
31
0
8
Order By: Relevance
“…ROI and sales growth and profitability evaluate financial performance; operational performance can be measured by market share, product launches, and market success rates; and organizational effectiveness can be measured by employee satisfaction and business enthusiasm. Because focusing especially on the financial index leads to an overemphasis on an organization's interior performance while neglecting external environmental performance (Úbeda-García et al, 2021). At the same time, Kaplan and Norton (1996) suggested the balanced scorecard process to increase conventional organizational performance measurements (Warahiu, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…ROI and sales growth and profitability evaluate financial performance; operational performance can be measured by market share, product launches, and market success rates; and organizational effectiveness can be measured by employee satisfaction and business enthusiasm. Because focusing especially on the financial index leads to an overemphasis on an organization's interior performance while neglecting external environmental performance (Úbeda-García et al, 2021). At the same time, Kaplan and Norton (1996) suggested the balanced scorecard process to increase conventional organizational performance measurements (Warahiu, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…GHRM has also been regarded as a proactive HRM response leading to better environmental outcomes (Gilal et al, 2019;Úbeda-García et al, 2022). Daily and Huang (2001) indicated that GHRM is a vital factor for successful environmental strategies and plays a unique role in dynamic organization behavior (Ansari et al, 2021;Saeed et al, 2019).…”
Section: Green Human Resource Management Green Transformational Leade...mentioning
confidence: 99%
“…Jackson and Seo (2010) considered GHRM as HRM practices in order to achieve the ultimate goal of environmental protection of companies by meeting environmental demands and organizing environmental resources (Paulet et al, 2021). GHRM has also been regarded as a proactive HRM response leading to better environmental outcomes (Gilal et al, 2019; Úbeda‐García et al, 2022). Daily and Huang (2001) indicated that GHRM is a vital factor for successful environmental strategies and plays a unique role in dynamic organization behavior (Ansari et al, 2021; Saeed et al, 2019).…”
Section: Theoretical Foundation and Research Hypothesesmentioning
confidence: 99%
“…GI is vital to enhance environmental performance (Úbeda García et al, 2022) and boost economic performance (Chen et al, 2006). To achieve win-win outcomes for sustainable environmental management and economic development, it is imperative to examine the determinants of GI.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%